Network Coding Based Reliable Multi-path Routing in Wireless Sensor Network - Zhao Wei; Tang Zhenmin; Yang Yuwang; Wang Lei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This thesis proposes a network coding based and easily-realizable composite network topologic model. It is composed of disjoint multi-path routing (DMR) and braided multi-path routing (BMR) in wireless sensor network, and network coding technology is also employed in our multi-path routing. With the use of the Node Coding technology and the multi-path technology, NC-RMR (Network Coding based Reliable disjoint and braided Multipath Routing) strengthens the network reliability, and meanwhile reduces the number of desired sub paths and helps to balance the network loads. Finally, its theoretic correctness and performance superiority was verified in the simulation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3711